A REVIEW PAPER ON AGRICULTURE MANAGEMENT - Ankit Kumar, Richa Sinha (International Journal of Modern Agriculture, 2021)
Agriculture has been practiced in every world country since ancient times as life sustaining activity, when other development industries have not even existed. In Indian context, India was a net food grain importer in the early 1960s and has now been emerged as exporter of numerous agricultural commodities. As a result of the effects of globalization, marketing and development have become the buzzwords in the agriculture industry, also the development in biotechnology, precision farming and use of various highly mechanized techniques have led to a paradigm change in the field of agriculture. In addition to the government’s unique focus on privatization, farmer associations, public private partnerships, entrepreneurs also have shifted towards the agricultural growth. Moreover, involvement of erudite person has also played a vital role in achieving the development in agriculture sector. With the advent of chemical manures, new and improved plant variety with less dependence on climatic condition due to technological advancement has improved the agriculture condition. In result, agriculture has emerged as amalgamation of science, business and commerce..